Becoming a fraternal organization: Insights from the Encyclical Fratelli Tutti - Zózimo, R.; Cunha, M. P.; Rego, J. (Journal of Business Ethics, 2023)
We uncover fundamental dimensions of the process through which organizations embed the practice of fraternity through embarking on an organizational journey in the direction of the common good. Building on the latest encyclical of Pope Francis, Fratelli Tutti, about fraternal and social friendship, we offer insight into the understanding of what it means to become a fraternal organization and reflect on the key ethical and paradoxical challenges for organizations aiming at collectively contributing to the common good. We add to previous work by characterizing this journey as a process involving unique ethical challenges that emerge from the paradoxes associated with this process and how this might change the nature of the relationships between organizations and others within the organizational landscape.